A methods engineering study on Does Enterprises - Ces, Kathy (College of Engineering, 1999)
DOES Enterprises, a firm that manufactures garments, is the company under study. The main objective of the study is to improve the productive efficiency of the said company. The researchers documented the system through observations, interviews and plant visits. The researchers systematically investigated the operations at the workplace through work study, particularly, method study and work measurement. The main problems of the company were disloyalty and low productivity. The researchers have generated and evaluated several alternatives and have come up with a feasible solution for the mentioned problems.